Vertically-bundled MRV system for climate change mitigation actions in rice cultivation, towards realising national climate goals - Trang, Vu Hong; Nelson, Katherine; Yen, Bui Tan; Cuong, Ong Quoc; Tran, Nguyen Bao (International Rice Research Institute, 2024)
Rice production plays a crucial role in global food security and national economies, but also contributes significantly to the emission of greenhouse gases (GHG). In Southeast Asian countries, rice production is responsible for a larger amount of GHG emissions than livestock or other crops, and the highest share of Methane, a gas 28 times more potent than Carbon dioxide in global warming potential (https://cfpub.epa.gov/ghgdata/nonco2/). Governments have announced strong commitments to reduce emissions across sectors, reflected in their NDCs, Net-Zero targets, and the Methane Pledge. However, the share of countries that have quantified mitigation actions in the rice sector is significantly low, at 17 among the 164 nations that have submitted new and updated NDCs by November 2022 (Vu et al., 2022). Having an MRV system to structurally and consistently track GHG emissions from rice cultivation activities is essential for nations to determine baseline emissions and set achievable mitigation targets, as well as to monitor progress. It will also provide reliable evidence for policymaking and the verification of reductions for climate finance purposes. The case study from Vietnam presents a cost-effective MRV system for data collection, monitoring, and validation of GHG mitigation practices across different scales: field, province, region, and nation. Data is consistently collected and processed within and across vertically-bundled tools, which enables cross data validation. This system allows for multi-stakeholder contribution, aggregation, and use of data, including farmers, field extensionists, agricultural management officers, private companies, and development partners. Rice activity data is geo-referenced and linked with field measurement tools and a Tier-2 GHG calculator for automatic GHG calculation. Therefore, it offers a transparent and useful database for farmers, rice producers, policymakers, verifiers, and other stakeholders for tracking progress and decision-making while enabling traceability and labelling of low-emission rice products. This MRV model is adaptable to other countries to improve the transparency of climate change mitigation action planning and implementation towards their climate goals